Strategic approaches to improve equine breeding and stud farm outcomes - Imdad Ullah Khan; Aswin Rafif Khairullah; Asfand Yar Khan; Atta Ur Rehman; Imam Mustofa (Veterinary World, 2025)
This review explores advanced strategies for enhancing fertility and optimizing reproductive outcomes in equine breeding programs. Horses, being seasonal breeders, present unique reproductive challenges influenced by environmental and physiological factors such as photoperiods, hormone cycles, and aging. Key approaches discussed include hormonal therapies, artificial light manipulation, and nutritional supplementation to improve ovulation and conception rates during the breeding season. Specific hormones such as gonadotropin-releasing hormone analogs, equine follicle-stimulating hormone, and progesterone are analyzed for their roles in synchronizing estrus and increasing ovarian activity. The document also emphasizes the significance of dietary strategies, particularly the inclusion of omega-3 fatty acids, L-arginine, and essential vitamins, in improving reproductive health. In addition, the review underscores the importance of stallion management, addressing factors such as testicular health, age, and environmental stress. Practical methods to mitigate seasonal infertility and improve foaling rates through better reproductive management of mares and stallions are detailed. These insights aim to assist stud farm owners in maximizing breeding efficiency and achieving higher economic returns. The primary goal of this review is to provide a comprehensive guide to practical interventions that increase the productivity and sustainability of equine breeding operations.